Whole‐Class Co‐Construction in a High School Spanish Classroom: A Conversation Analytic Perspective. Issue 1 (26th October 2021) - Wagner, Santoi; Park, Innhwa
Abstract: This study demonstrates how conversation analysis can illuminate the interactional practices through which the Present‐Attention‐Co‐construction‐Extension (PACE) approach to grammar instruction, which involves a guided, inductive co‐construction of grammar rules with learners, is realized in the classroom. The data consist of three whole‐class Co‐construction discussions that occurred in three high school Spanish lessons on the pronoun se in non‐agentive constructions. We trace how the discussion unfolded and find that the key locus for the Co‐construction process was the work done by the teacher in the third turns of IRE sequences, and in particular, the withholding of explicit teacher assessment. We examine how the students treated and responded to such teacher third turns and how these sequences exhibited various interactional outcomes, such as a cyclical pattern of discourse, and misalignment of teacher and student focus. We consider the implications for a guided induction approach. Abstract :